KEEFEKTIFAN PERMAINAN PUZZLE KANJI PADA PEMBELAJARAN KANJI II MAHASISWA PROGRAM STUDI PENDIDIKAN BAHASA JEPANG ANGKATAN 2017/2018 - Sari, Melyana; Hadriana, Hadriana; Rahayu, Nana (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: The lack of motivation in learning Kanji was caused by the large number of Kanji that students needed to learn in one meeting. It was also caused by the conventional learning technique that made students feel saturated. This research aimed to find out the effectiveness of applying Kanji puzzle game in increasing the learning outcomes of Kanji subject on Japanese Study Program academic year 2017/2018. This research used weak experiment with the design of pretest-posttest class or one group pre-test post-test. The sample of this research consisted of 32 students of class A from Japanese study program academic year 2017/2018. This research used purposive sampling technique where it was used for particular criteria or purposes. The data were collected by distributing test. The test was divided into pre-test and post-test. After the pre-test and post-test data gathered, then they were processed by using SPSS Version 24 IBM for windows.Based on the data analysis, the average score of pre-test was 67 and the average score for post-test was 84. After applying t-test, it was obtaind that the value of sig (2-tailed) was 0,000 < 0,05. Because the value of sig (2-tailed) was 0,000 smaller than 0,05, it could be concluded that the use of Kanji puzzle game technique can increase students class A learning outcomes in Kanji subject. It proved that Ho hypotesis was rejected and Ha was accepted. Thus, the use of Kanji puzzle game was effective in increasing Students’ Kanji subject learning outcomes of Japanese Study Program academic year 2017/2018.Key Words: Kanji, Puzzle, The effectiveness.